THE USE OF THREE STEPS INTERVIEW TO IMPROVE SPEAKING SKILL FOR TENTH GRADE OF HOSPITALITY STUDENTS AT SMKN 8 SURABAYA - Satria, Hana (English Language Education Study Program, 2022)
The paper is aimed to find out whether the Three Steps Interview can improve the students speaking skill in Tenth Grade of Hospitality SMKN 8 Surabaya. Participants in this study were tenth graders majoring in hospitality. There are 36 students in the class. From that, the number of female students dominates. The data used in this research were students difficulty to the learning process and students speaking score. From this information, the researchers could find that the treatment was successful or not. To collect the data, the researchers used instruments such as test and observation checklist. In the first cycle the students' speaking ability has not increased. This is caused by several things, such as (1) Unclear explanation of the material, (2) in group division, students choose groups independently so that students who are smart and those who are less intelligent cannot be divided equally. (3) The teacher explaining the material is less relaxed. (4) Instructions are not clear. (5) The teacher determining the topic by his-self. In the second cycle students' speaking ability increased from 85% of students got score 50 to 69 and 15% got scores in the range of 70 to 84 increase into 91% students succeeded in achieving the criteria for the value that must be achieved. In conclusion, the Three Steps Interview technique can be used to improve speaking skills.